L-LOP/LOPP for the treatment of canine gastrointestinal/hepatosplenic lymphoma - Lai, Yu Ying; Horta, Rodrigo dos Santos; Almendros, Angel; Ha, Patrick W. Y.; Giuliano, Antonio (Frontiers in Veterinary Science, 2024)
Canine gastrointestinal (GI) and hepatosplenic (HS) high-grade (large cell) lymphomas are uncommon forms of canine lymphomas, with a very poor response to chemotherapy and a very poor prognosis. Currently, there are no established effective chemotherapy protocols for canine GI/HS lymphomas. This case series aimed to retrospectively evaluate the efficacy of lomustine-based protocols L-LOP (L-asparaginase, lomustine, vincristine, and prednisolone) and L-LOPP (with the addition of procarbazine) for treatment of canine GI/HS lymphomas. Medical records of dogs with cytologically or histologically diagnosed lymphoma at CityU Veterinary Medical Centre from 2019 to 2022 were retrospectively reviewed. Median progression-free survival for GI and HS lymphoma was 56 days (range, 10 to 274 days) and 57 days (range 8-135 days) respectively; while median survival time for GI and HS lymphoma was 93 days (range 10-325 days) and 210 days (range 8 to 240 days) respectively. The absence of clinical improvement after chemotherapy, gastric involvement of the lymphoma and ascites at initial presentation was associated with a shorter survival time in dogs with both GI and HS lymphoma.